2021
DOI: 10.5194/tc-2021-162
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deep ice as a geochemical reactor: insights from iron speciation and mineralogy of dust in the Talos Dome ice core (East Antarctica)

Abstract: Abstract. Thanks to its insolubility, mineral dust is considered a stable proxy in polar ice cores. With this study we show that below an ice-depth of 1000 m, the Talos Dome ice core (Ross Sea sector of East Antarctica) presents evident and progressive signs of post-depositional processes affecting the mineral dust records. We applied a suite of established and cutting edge techniques to investigate the properties of dust present in the Talos Dome ice core, ranging from concentration and grain-size to elementa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…Based on the imaging afforded by LA‐ICP‐MS, image analysis techniques can be applied for selecting particle clusters that are located at, or in touch with, grain boundaries. Comparing the chemical signature, especially related to Fe, of particles at grain boundaries versus interiors could help to refine further the recently proposed view of deep ice as a “geochemical reactor,” expecting post‐depositional chemical reactions within the acidic environments of grain boundaries (Baccolo et al., 2021). In light of ongoing efforts to retrieve an “Oldest Ice Core” from Antarctica, it becomes clear that the special merit of the LA‐ICP‐MS technique goes beyond providing 1‐D impurity profiles at micron resolution.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Based on the imaging afforded by LA‐ICP‐MS, image analysis techniques can be applied for selecting particle clusters that are located at, or in touch with, grain boundaries. Comparing the chemical signature, especially related to Fe, of particles at grain boundaries versus interiors could help to refine further the recently proposed view of deep ice as a “geochemical reactor,” expecting post‐depositional chemical reactions within the acidic environments of grain boundaries (Baccolo et al., 2021). In light of ongoing efforts to retrieve an “Oldest Ice Core” from Antarctica, it becomes clear that the special merit of the LA‐ICP‐MS technique goes beyond providing 1‐D impurity profiles at micron resolution.…”
Section: Discussionmentioning
confidence: 91%
“…This concerns not only systematic changes in their size distribution by forming of aggregates (Lambert et al., 2008). Recently it was shown that englacial chemical reactions between dust particles and acidic environments formed within grain boundaries can result in post‐depositional alteration of their geochemical signature (Baccolo et al., 2021). Both size distribution and geochemical composition are valuable indicators of past atmospheric transport and dust sources (Albani et al., 2012; Baccolo et al., 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The ABD-based volumes are converted to mass using the FD066 density, 3.96 g/cm 3 . Similarly prepared samples are measured by Coulter Counter at the University of Milano-Bicocca, by adopting the same analytical steps as described in (Baccolo et al, 2021). The LOD of the CC, calculated as 3 standard deviations above the average of n=7 UPW samples, is 10 ppb.…”
Section: Standard Reference Material: Size Reconstruction Lods and Ma...mentioning
confidence: 99%